The Effect of Formal Performance Evaluation and Efficacy on Supervisor Trust in Employees with Remote Working - Shalihani Humaira; Sriwidharmanely Sriwidharmanely (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study examines the effect of formal performance evaluation and efficacy on supervisors' trust in remote employees. One important way to create effective performance is the trust of superiors in their subordinates and vice versa. Remote working means employers and employees don't have to meet in person to get work done. This research uses the Leadership Member Exchange (LMX) leadership theory. Leadership Member Exchange (LMX) theory is the perception of interaction between superiors and employees. This article examines how efficacy can strengthen employers' trust in their employees' data in remote work. Still, formal performance evaluations do not have the effect obtained using online questionnaire survey data. The method in this study used multiple regression.